2013
DOI: 10.1002/ange.201309094
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrosilation of CO2 to a Bis(silylacetal) Using an Anilido Bipyridyl‐Ligated Organoscandium Catalyst

Abstract: A rigid anilido bipyridyl ligand has been designed for use in an organoscandium-based carbon dioxide hydrosilation catalyst. Ligand attachment by alkane elimination results in metalation of an aryl CÀH bond in a 3,5-di-tertbutylphenyl group installed on the pyridyl unit, thus rendering the ligand tetradentate. Insertion of CO 2 into the newly formed Sc À C bond leads to a k 1 carboxylate which, when treated with the borane B(C 6 F 5 ) 3 , becomes hemilabile. In addition to activating the catalyst, the k 1 carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Most commonly used and well-studied photo-initiatable catalysts are platinum-based ones such as a A novel method for obtaining α-silyl carbonyl products using B(C 6 F 5 ) 3 as catalyst was reported by Kim and Chang [69]. Unlike previously reported hydrosilylations of unsaturated polar bonds (such as carbonyls, imines, and nitriles [70][71][72]), the authors demonstrated the feasibility of the chemoselective α-silylation of conjugated esters and amides, in which the carbonyl group was left intact (Figure 29). According to preliminary mechanistic studies, the reaction proceeds in two steps, namely rapid 1,4-hydrosilylation of conjugated carbonyls and slow silyl group migration of a silyl ether intermediate.…”
Section: Light-initiated Hydrosilylation Reactionsmentioning
confidence: 99%
“…Most commonly used and well-studied photo-initiatable catalysts are platinum-based ones such as a A novel method for obtaining α-silyl carbonyl products using B(C 6 F 5 ) 3 as catalyst was reported by Kim and Chang [69]. Unlike previously reported hydrosilylations of unsaturated polar bonds (such as carbonyls, imines, and nitriles [70][71][72]), the authors demonstrated the feasibility of the chemoselective α-silylation of conjugated esters and amides, in which the carbonyl group was left intact (Figure 29). According to preliminary mechanistic studies, the reaction proceeds in two steps, namely rapid 1,4-hydrosilylation of conjugated carbonyls and slow silyl group migration of a silyl ether intermediate.…”
Section: Light-initiated Hydrosilylation Reactionsmentioning
confidence: 99%
“…3 Although most of the reported systems use heterogeneous catalysts, some homogeneous transition-metal based catalytic systems have been developed for the reduction of CO2 to formic acid, 4 formate, 5 formaldehyde, 6 methanol, 7 methane 8 and acetals. 9 Organocatalysts, as species not comprised of transition metals, are still scarce in the field of CO2 functionalization to valuable chemicals. 10 Notable systems include highly Lewis acidic aluminum species 11 and silyl cations 12 which have been shown to reduce CO2 with low selectivity to mixtures of products comprising methane, methanol and a number of alkylation byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…A structurally related NNN ligand platform 8-amino-2-(pyrid-2′-yl)quinoline has been prepared and complexed to Sc. 26,27 Lithiation of 8-bromo-2-(pyrid-2′yl)quinoline with butyl lithium gave 8-lithio-2-(pyrid-2′yl)quinoline, which reacted readily with i Pr 2 PCl to give the corresponding tertiary phosphine iPr PQpy. Prepared analogously using (C 6 F 5 ) 2 PCl was the bis(pentafluorophenyl)phosphine derivative ArF PQpy (Scheme 1).…”
Section: ■ Resultsmentioning
confidence: 99%